Legal Protection for Dentists Against Unauthorized Video Recording by Patients in Clinical Environments - Aditya Pratama Sarwono; Ahmad Redi (Yayasan Adra Karima Hubbi, 2024)
The widespread use of smartphones with video recording features has significantly impacted interactions in healthcare settings. Unauthorized recordings by patients, especially during clinical interactions, are becoming more common. Such recordings often lead to privacy concerns, legal challenges, and a breakdown of trust. Some patients use these recordings to demand refunds, threatening to make the videos viral if their demands are not met, thereby compromising healthcare professionals' privacy and creating an intimidating atmosphere that affects care quality. This study aims to examine legal protections for dentists against unauthorized recordings by patients, highlighting the need for clear regulations and public education on the rights and responsibilities of healthcare providers and patients. A qualitative approach was used, involving interviews with dentists to explore their experiences with unauthorized recordings. Relevant legal documents were analyzed to understand the current legal framework, and regulations from other countries were compared to evaluate how different jurisdictions address unauthorized recordings in healthcare. The study found that current regulations in Indonesia, such as the Information and Electronic Transactions Law and the Personal Data Protection Law, provide insufficient protections for healthcare providers. Unauthorized recordings by patients often lead to privacy violations and reputational damage to dentists. More explicit regulations are needed to protect healthcare providers from unauthorized recordings, supported by effective enforcement and public education on privacy rights. Clear legal guidelines and proactive policies can better protect healthcare providers and maintain a therapeutic relationship with patients.